Archiving of Records in Kanungu Local Government Registry. - Atuhaire, Catherine (Kabale University, 2024)
This study investigated archival records practices in Kanungu Local Government Registry. The objectives of the study were to find out the types of records maintained at Kanungu Local Government Registry, identify the records processes involved in archiving records, to investigate challenges faced by records officers in archiving records, and suggest measures to improve the archiving of records in Kanungu Local Government. A qualitative case study research design was used. Data was collected using interviews, documentary review, and observation methods. A total of 15 respondents were selected using a purposive sampling technique. Data was analyzed using content analysis and thematic analysis. The finding revealed that historical records, policy documents, minutes of meetings, financial documents, employment records, incoming and outgoing documents, and financial statements were some of the records kept in the Kanungu Registry. The record processes involved in archiving records involved grouping similar types of records together, separating folders containing low-value information, use of archival boxes to store the files, assigning the collection labels, and surveying the collection to gain an understanding of its condition and contents. The challenges faced by records officers in archiving records included; lack of enough data capture tools, inadequate training skills for record staff, integration of records systems, risk of fire, water, and rats, uncoordinated officers working in a similar co-operation, short retention periods for archiving records, costs associated with maintaining records, limited storage space of the achi val repository. The proposed strategies for improving the archival of records in the registry involved monitoring and evaluation process, implementation of policies that govern archives storage, staff training, and a strategic plan. The study recommends that the Kanungu local government Registry should be availed with more storage space and professional records officers to improve the quality of information services provided IO the people of the Kanungu district. The processes involved in archiving records in the Registry should be improved to avoid delays in records archiving.